1974
DOI: 10.1161/01.cir.49.6.1078
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol in the Treatment of Acute Myocardial Infarction

Abstract: Improvement of myocardial oxygenation is a major goal in the treatment of ischemic heart disease. Propranolol, 0.1 mg/kg intravenously, was administered to 20 patients in the acute state of myocardial infarction without clinical evidence of left ventricular failure. The most important hemodynamic response was a substantial decrease in myocardial contractility. This was reflected by a fall i cardiac index (average of 0.6 L/min/M2, P < 0.001) and of arterial mean pressure (average of 16 mm Hg, P < 0.001) with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…A reduction of coronary blood flow after propranolol associated with a widening of the arterial-coronary sinus oxygen difference has suggested a vasoconstrictor effect,34 3 while narrowing of transcoronary oxygen difference after,8 blockade is consistent with reduction of myocardial metabolism. 23 The increase in myocardial oxygen consumption due to the elevated rate-pressure product during CPT was associated with an inappropriate increase in coronary vascular resistance in patients with CAD. 4 The potentiation of coronary vascular resistance during CPT after ,3-adrenergic blockade occurred with identical CPT-induced changes in the ratepressure product, suggesting that enhanced a-adrenergic tone, rather than diminished myocardial metabolic demand, was responsible for the further increase in coronary vasoconstrictor tone.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of coronary blood flow after propranolol associated with a widening of the arterial-coronary sinus oxygen difference has suggested a vasoconstrictor effect,34 3 while narrowing of transcoronary oxygen difference after,8 blockade is consistent with reduction of myocardial metabolism. 23 The increase in myocardial oxygen consumption due to the elevated rate-pressure product during CPT was associated with an inappropriate increase in coronary vascular resistance in patients with CAD. 4 The potentiation of coronary vascular resistance during CPT after ,3-adrenergic blockade occurred with identical CPT-induced changes in the ratepressure product, suggesting that enhanced a-adrenergic tone, rather than diminished myocardial metabolic demand, was responsible for the further increase in coronary vasoconstrictor tone.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, specific blockade of /3-adrenoceptor stimulation has been found to reduce the severity of initial ischaemic injury (Maroko et al, 1971) following coronary ligation and to minimize the extent of subsequent necrosis (Reiner, Rasmussen & Jennings, 1973). A favourable action on the metabolism of ischaemic myocardium in animals (Haneda et al, 1973) as well as man (Mueller et al, 1974) has also been noted, a finding significant in relation to the claimed beneficial effect of p-adrenoceptor blockade on long-term prognosis of patients following acute myocardial infarction (Wilhelmsson et a/., 1974). These observations are thus at variance with the results of studies (Balcon et al, 1966;Clausen et al, 1966;Norris et al, 1968), which showed that /I-adrenoceptor blockade had no effect on early hospital mortality in patients with acute myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of propranolol, it is possible that relatively large initial oral doses may ensure high plasma drug levels early by rapid saturation of hepatic binding capacity of the drug. Alternatively, the loading doses may be administered intravenously since Mueller and her colleagues (Mueller et a/., 1974) have recently shown that 0.1 mg/kg propranolol by this route improves myocardial oxygenation in patients with uncomplicated infarction without producing serious adverse effects. It may also be necessary to undertake a variable rather than a fixed dose trial, so that the dose used can be appropriately adjusted individually to produce a defined degree of sympathetic blockade as indicated by alterations in heart rate and plasma drug concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Since fi-adrenoceptor blockade is widely used in cardiovascular disease and there is a growing interest in the use offi-adrenoceptor blockade for reduction of myocardial ischemia (Waagstein, Hjalmarson & Wasir, 1974;Mueller et aL, 1974;Waagstein & Hjalmarson, 1975a, b), patients arriving in coronary care units will frequently be under such medication.…”
Section: Introductionmentioning
confidence: 99%